Robot‐assisted pancreatic surgery: a systematic review of the literature. Issue 1 (17th October 2012) - Strijker, Marin; van, Hjalmar C.; Besselink, Marc G.; van, Richard; Borel Rinkes, Inne H.M.; Vriens, Menno R.; Molenaar, I. Quintus
Abstract Background To potentially improve outcomes in pancreatic resection, robot‐assisted pancreatic surgery has been introduced. This technique has possible advantages over laparoscopic surgery, such as its affordance of three‐dimensional vision and increased freedom of movement of instruments. A systematic review was performed to assess the safety and feasibility of robot‐assisted pancreatic surgery. Methods The literature published up to 30 September 2011 was systematically reviewed, with no restrictions on publication date. Studies reporting on over five patients were included. Animal studies, studies not reporting morbidity and mortality, review articles and conference abstracts were excluded. Data were extracted and weighted means were calculated. Results A total of 499 studies were screened, after which eight cohort studies reporting on a total of 251 patients undergoing robot‐assisted pancreatic surgery were retained for analysis. Weighted mean operation time was 404 ± 102 min (510 ± 107 min for pancreatoduodenectomy only). The rate of conversion was 11.0% (16.4% for pancreatoduodenectomy only). Overall morbidity was 30.7% (n = 77), most frequently involving pancreatic fistulae (n = 46). Mortality was 1.6%. Negative surgical margins were obtained in 92.9% of patients. The rate of spleen preservation in distal pancreatectomy was 87.1%. Conclusions Robot‐assisted pancreatic surgery seems to be safe and feasible in selected patients and, in left‐sided resections, may increase the rate of spleen preservation. Randomized studies should compare the respective outcomes of robot‐assisted, laparoscopic and open pancreatic surgery.